Determinants of potential buyer purchase intention toward life insurance among generation Y - Ooi, Jonathan Wei Keat; Leh, Khai Heng; Lim, Weng Kai; Lye, Ka Hang; Ong, Huey Yin (2019)
The aim of this research is to study the determinants of potential buyer purchase intention toward life insurance among generation Y. Independent variables (IVs) including attitude, social influence, income and knowledge are used to test whether they are able to affect the dependent variable (DV) which is purchase intention toward life insurance among generation Y. Thus, the relationship between each IV and DV will be discussed further in our research. There is a total of 292 sets of questionnaires had successfully collected and all the data collected has been analysed through the Statistical Package for the Social Sciences (SPSS) software. The inferential analysis such as Pearson Correlation Coefficient and Multiple Regression Analysis had adopted to indicate the relationship between IVs and DV. In a nutshell, the results obtained for this research show the three independent variables including attitude, social influence and knowledge have a significant relationship with DV. While income is the only IV that has no significant relationship with DV. The overview of the major findings, implications, limitation and recommendations have been studied in this research.